The structural outcomes of investment surges - Mateo Hoyos; Emiliano Libman; Arslan Razmi (University of Massachusetts, Department of Economics, 2021)
We study the extent to which countries undergo structural change during and after episodes of sustained investment surges. In particular, we explore the evolution of trade flows, considering (i) exports sophistication or complexity, (ii) exports diversification, and (iii) capital goods imports. Using the episodes identified by Libman et al. (2019), we document the heterogeneous nature of these episodes and find that, while imports of capital goods increase, they are not systematically related to changes in sophistication, complexity and diversification of exports, at least for the available sample of 130 episodes over the period 1962-2014. High investment may often be a necessary but not sufficient condition for structural change.
Keywords: E22; F41; O11; 330; Capital accumulation; diversification; economic complexity; development